MENENTUKAN STRATEGI PERMASARAN PADA PRODUK BRIKET DENGAN METODE GAME THEORY UNTUK MENINGKATKAN PENJUALAN DI UKM KAISAR BRIKET - Satria Ramadhani; Boy Isma Putra (Universitas Ahmad Dahlan Indonesia, 2015)
UKM Kaisar Briket is one of the business sectors that briket produce. The problem is not enough briket product known to the public and the market competition, briket product compete with LPG and kerosene so that the competition is encouraging to be albe to search for the right marketing to strategy to compete in the market.the methode game theory can deetermine a marketing strategy through the marketing mix 4P (product, price, place, promotion). Marketing mix divided into severval attribute to know some of the marketing strategy that will be product advantage to attract users briket. Responden data required to obtain the value of matriks calculation game theory methode previously in reliability test and validitas test toknow what valid whether or not the responden data the result of the study showed the briket product have superior strategy and alternative strategies when competitions products. Keyword : marketing, marketing mix, game theory